Newborn Mortality in Sub-Saharan Africa: Why is Perinatal Asphyxia Still a Major Cause? - Fatima Usman; Abdulazeez Imam; Zubaida L. Farouk; Aliyu L. Dayyabu (Ubiquity Press, 2019)
Abstract Global new-born mortality has shown steady decline over the last two decades, but this decline has been slowest in Sub-Saharan Africa (SSA). Perinatal asphyxia (PA) is a major cause of new-born deaths in this region and as such SSA now contributes a disproportionate large percentage of global asphyxia-related deaths. In this paper, we examine regional challenges affecting primary, secondary and tertiary prevention of PA and proffers locally adaptable solutions to these identified challenges.